Salt Stress Tolerance and Germination Performance Of Mungbean Genotypes Under Salt Stress (Bangladesh Agronomy Journal, 2022)
Sea level rising, as a result of global warming, is a major threat to crop production; because inclusion of saline water in crop land limits the crop production. So, an experiment was undertaken to evaluate some mungbean genotypes under different levels of salt stresses in germination stage. The experiment was conducted at Regional Agricultural Research Station, Jashore during Rabi 2020-2021. The seeds of seven mungbean genotypes viz. BARI Mung-6, BARI Mung-8, BMXKI-112004-3, BMXKI- 112009-21, MMAT-V07, BMMP-201524 and BMMP-201506 were collected from different sources. This experiment was conducted following factorial completely randomized design (CRD) with two replications. The experimental factors were i) mungbean genotypes (seven) and ii) salt stress (three levels: 0, 4 and 8 dSm-1). The results showed that mungbean var. BARI Mung-6 at 0 dSm-1 and 4 dSm-1 showed highest value in case of germination index (9), germination percentage (100%), co-efficient of germination (40), vigor index (1950) and lowest value in case of mean germination time (2.5). BARI Mung-8 at 0 dS m-1 showed the inverse results. Genotype BMXKI-112009- 21, MMAT-V07 and BMMP-201524 at 4 dSm-1 and in some extent in 8 dSm-1 showed highest value in case of germination stress tolerance index, plant height stress index, root length stress index, shoot fresh weight stress index, root fresh weight stress index, shoot dry weight stress index and in root dry weight stress index. The lowest values in these parameters were found in BARI Mung-8 at 8 dSm-1 salt stress. BARI Mung-6, MMATV07, BMXKI-112009-21 and BMMP-201524 genotypes were found to be more tolerant to salt stress than rest of the genotypes in germination stage.Bangladesh Agron. J. 2022, 25(1): 57-65